Revealing Gylfi's Illusion: A Systematic Analysis and Proposed Astronomical Interpretation of Mythological Elements in Gylfaginning (as transcribed from GKS 2367 4to) - Ryan Thomas Eckerson 1992- (2024)
This thesis demonstrates that Gylfaginning, the main mythological narrative of Snorri’s Edda, contains obvious celestial references that navigate the reader or listener through the Norse cosmos as depicted in the night sky above Iceland and Scandinavia. To demonstrate this, the author records every obvious celestial reference to air/sky/heavens found in the Gylfaginning narrative. He then provides a systematic analysis of every celestial reference as they occur page-by-page in Gylfaginning. Prior attempts to astronomically interpret the Norse myths have utilized planetary movements to represent the movement of the gods. Some interpretations have suggested that verses 5 and 6 of Völuspá provide the basis for determining where the gods’ homes are located in the night sky. The author analyzes these methods and then suggests a new astronomical interpretation of various Norse mythological elements in Gylfaginning by utilizing the eighth sphere of the Aristotelian model of cosmology, the sphere of fixed stars. Þessi ritgerð sýnir fram á að Gylfaginning, helsta goðsögulega frásögn Snorra-Eddu, hefur að geyma augljósar himneskar tilvísanir sem taka lesandann eða hlustandann í ferðalag um norræna alheiminn eins og hann er sýndur á næturhimninum fyrir ofan Ísland og Skandinavíu. Til að sýna fram á þetta skráir höfundur hverja augljósa himnesku tilvísun til lofts/himins sem finnast í Gylfaginning frásögninni. Hann gefur síðan kerfisbundna greiningu á hverri himneskri tilvísun eins og þær koma fyrir blaðsíðu fyrir blaðsíðu í Gylfaginning. Fyrri tilraunir til að túlka norrænu goðsagnirnar á stjarnfræðilegan hátt hafa notað hreyfingar plánetanna til að tákna hreyfingu guðanna. Sumar túlkanir hafa bent til þess að 5. og 6. vers í Völuspá séu grundvöllur þess að ákvarða hvar heimili guðanna eru staðsett á næturhimninum. Höfundur greinir þessar aðferðir og stingur síðan upp á nýrri stjarnfræðilegri túlkun á ýmsum norrænum goðafræðilegum þáttum í Gylfaginning með því að nýta áttundu kúlu heimsfræðilíkansins Aristótelíu, kúlu ...